Atmospheric Microplastics: Inputs and Outputs - Christine C. Gaylarde; José Antônio Baptista Neto; Estefan M. da Fonseca (Micro, 2025)
The dynamic relationship between microplastics (MPs) in the air and on the Earth’s surface involves both natural and anthropogenic forces. MPs are transported from the ocean to the air by bubble scavenging and sea spray formation and are released from land sources by air movements and human activities. Up to 8.6 megatons of MPs per year have been estimated to be in air above the oceans. They are distributed by wind, water and fomites and returned to the Earth’s surface via rainfall and passive deposition, but can escape to the stratosphere, where they may exist for months. Anthropogenic sprays, such as paints, agrochemicals, personal care and cosmetic products, and domestic and industrial procedures (e.g., air conditioning, vacuuming and washing, waste disposal, manufacture of plastic-containing objects) add directly to the airborne MP load, which is higher in internal than external air. Atmospheric MPs are less researched than those on land and in water, but, in spite of the major problem of a lack of standard methods for determining MP levels, the clothing industry is commonly considered the main contributor to the external air pool, while furnishing fabrics, artificial ventilation devices and the presence and movement of human beings are the main source of indoor MPs. The majority of airborne plastic particles are fibers and fragments; air currents enable them to reach remote environments, potentially traveling thousands of kilometers through the air, before being deposited in various forms of precipitation (rain, snow or “dust”). The increasing preoccupation of the populace and greater attention being paid to industrial ecology may help to reduce the concentration and spread of MPs and nanoparticles (plastic particles of less than 100 nm) from domestic and industrial activities in the future.